SYK Is Associated With Malignant Phenotype and Immune Checkpoints in Diffuse Glioma - Zhou, Quanwei; Wei, Min; Shen, Wenyue; Huang, Sheng; Fan, Jianfeng; Huang, He (Frontiers in Genetics, 2022)
Background Diffuse glioma, the most common intracranial malignant tumor, is characterized by immunosuppression. The prognostic significance and potential therapeutic value of SYK remain obscure. Here, we attempted to explore the performance of SYK in predicting prognosis and therapeutic targets. Methods The mRNA expression and clinical data for pan-cancers and normal tissues and more than 2000 glioma samples were collected from public databases. The expression level of SYK was evaluated by qPCR and IHC. The prognostic value of SYK was assessed using the Kaplan-Meier curve and univariate and multivariate cox regression analysis. A sequence of immune and stromal cell infiltration analysis was calculated based on the ESTIMATE algorithm, ssGSEA algorithm, or TIMER. The SYK-related subtypes were identified via a Consensus Cluster Plus analysis. Results SYK was significantly differentially expressed in the multiple tumors and normal tissues. Importantly, high-expression SYK was enriched in malignant phenotypes of diffuse gliomas, which was further validated by qPCR and immunohistochemistry. Survival analysis uncovered that SYK was an independent indicator of poor prognosis in diffuse glioma. Functional enrichment analysis and immune and stromal infiltration analyses showed the aberrant expression of SYK was involved in shaping the immunosuppressive microenvironment of diffuse glioma. Additionally, SYK expression was closely associated with some immune checkpoint molecules and M2 macrophages infiltration. The association between SYK and CD163 and PD-L1 was validated by immunohistochemistry. Diffuse glioma with Sub1 exhibited a worse prognosis, immunosuppressive microenvironment, and higher expression of immune checkpoint genes. Conclusions SYK was involved in shaping the immunosuppressive microenvironment and served as a promising prognosis biomarker and immunotherapeutic target for diffuse glioma.